A group-level approach to analyzing participative ergonomics (PE) effectiveness: The relationship between PE dimensions and employee exposure to injuries. (April 2018) - Morag, Ido; Luria, Gil
Abstract: Most studies concerned with participative ergonomic (PE) interventions, focus on organizational rather than group level analysis. By implementing an intervention at a manufacturing plant, the current study, utilizing advanced information systems, measured the effect of line-supervisor leadership on employee exposure to risks. The study evaluated which PE dimensions (i.e., extent of workforce involvement, diversity of reporter role types and scope of analysis) are related to such exposure at the group level. The data for the study was extracted from two separate computerized systems (workforce medical records of 791 employees and an intranet reporting system) during a two-year period. While the results did not confirm the effect of line-supervisor leadership on subordinates' exposure to risks, they did demonstrate relationships between PE dimensions and the employees' exposure to risks. The results support the suggested level of analysis and demonstrate that group-based analysis facilitates the assimilation of preventive interventions. Highlights: PE intervention is validated at the group rather than at the organizational level. Group level analysis is new to studies of PE interventions. The relative effect of PE dimensions on workforce safety is quantitatively measured. Applying PE dimensions at group level significantly reduces workforce injuries.